Clinical, haematological and biochemical effects of detomidine and ketamine anaesthesia in dogs - JADON, N S; KUMAR, AMRESH; SINGH, HARNAM; SINGH, HARPAL (The Indian Journal of Animal Sciences, 2013)
Intramuscular administration of detomidine (0.2 mg/kg) followed by ketamine (5 mg/kg) in atropine sulphate (0.04 mg/kg) premedicated dogs (12) resulted in onset of anaesthesia in 6.4±2.3 min. The duration of anaesthesia lasted for 41.30±5.35 min and recovery occurred in 62.60±5.60 min. There was a significant (P<0.05) increase in total lencocyte count with a nonsignificant effect on lotal erythrocyte count, packed-cell volume, haemoglobin and blood clotting time, The biochemical changes included a significant (p<0.05) increase in plasma glucose with a nonsignificant increase in plasma urea nitrogen, creatinine and alanine amino transferase and nonsignificant decrease in plasma total protein and albumin. Gastrotomy, end-to-end anastomosis of intestine, splenectomy, cystotomy and ovario-hysterectomy, were successfully performed under atropine- detomidine-ketamine anaesthesia in 30 dogs. The anaesthesia and muscle relaxation were good and recovery was smooth and uncomplicated.